Humanizing English Language Pedagogy: A Case Study of Kathmandu Valley School in Nepal - Paneru, Narendra Raj (AMC Multidisciplinary Research Journal, 2025)
This paper highlights the prevailing practices of dehumanized ELT pedagogies in Nepal, with a special focus on issues like cultural insensitivity, language hegemony, rote learning strategies, teacher-centered approaches, non-differentiation of teaching, and limited authentic language use. Employing the generic qualitative approach, this study used tools such as interviews, observations, and focus group discussions with purposively selected six English language teachers and eight students from six schools in Kathmandu Valley to retrieve data to explore the issues of dehumanization and humanizing strategies in ELT practices and their implications for diverse language learners in the context of Nepal. The study found that there are dehumanizing practices in the Nepali ELT milieu, and they can be humanized using soft skills, culturally responsive pedagogy, and student-centered learning.